Narratives of Globalisation and Their Implications for Education - Humes, Walter (2014)
This paper begins by noting the way in which education as a disciplinary field ishighly dependent on concepts that have their origins in other spheres of knowledge.It draws attention to the deployment by international agencies of termsthat can be applied across a range of disciplines and to a growing tendency amongdeveloped countries to conceptualise their educational priorities in similar forms ofdiscourse. However, it is also noted that pressures to converge are, to some extent,offset by local values and traditions which serve to maintain degrees of divergence.The paper then focuses more sharply on the various dimensions of globalisationwhich have implications for education, drawing attention to definitional problemsand to the malleable character of the territory. This is followed by two contrastingsections, one looking at positive narratives of globalisation in education, theother taking a more critical perspective. It is concluded that while globalisation asa concept has some explanatory power, the purposes to which it is put by differentagencies require careful interrogation. Furthermore, the time may come when itsvalue in policy documents diminishes and new discursive forms may emerge. In themeantime, education professionals should seek to develop greater narrative agencyin interpreting the language of globalisation.